Awareness of Dental Health Checkup omong the Patients Attending at Selected Hospital in Dhaka City - Karim, MM; Alif, SM; Tarafder, MA; Sharmin, D; Khan, MH (Bangladesh Journal of Dental Research & Education, 2013)
This descriptive type of cross sectional study was conducted in selected hospital of Dhaka in order to find out the awareness of dental health check up among the patient in selected hospital in Dhaka city. The study was conducted from September to December 2011 with sample of 150. Results revealed that there is a huge difference between the awareness and practice on oral hygiene. The study showed that most of the respondents are in between 30-39 years of age (39.3%), 22.7% in 20-29 years of age, only very few 0.7% in > 70 years of age with mean age 35.75 + 12.03. Among the respondents 34.7% are housewife, service holder 28%, business 15.3% and others are 22%. Study also showed that 65.3% brushes their teeth once daily and 34.7% in twice daily, 52% brushes only before breakfast, 18.7% before breakfast and before go to bed, 15.3% after breakfast and before go to bed, 12% only after breakfast and rest 2% only before go to bed. Among the respondents 38% visit to dentist more than 1 years for cleaning purpose, 28.7% visit after 1 year, 23.3% visit within 6 months to 1 year and very few only 10% visit before 6 months. Most of the respondent about 66% knows that consumption of sweet food can cause caries and rest 34% have no idea. About 40% feels the necessity of visiting dental surgeon after 1 year, 28% feels the time is after 6 months, 17.3% feels that more than 1 year and 14.1% have no idea. There is statistically highly significant association between the age of the respondent and the material used for cleaning teeth , sex of the respondent and habit of taking tobacco in both association (P = 0.000). Another statistically highly significant association between occupation of the respondent and habit of taking tobacco and also between age of the patient and habit of chewing areca nut and lime (P = 0.000), between frequency of cleaning teeth and monthly income of the respondent (P = 0.050). Another statistically significant association between age of the respondent and knowledge about sweet food can cause dental caries where (P = 0.023). and between monthly income of the respondent and knowledge about sweet food can cause dental caries (P = 0.013). From the study results it is revealed that only 30-39 years old patients aware about dental health check up, most of patient brushes their teeth only before breakfast, visit to dental surgeon visit to dentist more than 1 years for cleaning purpose, and feels the necessity of visiting dental surgeon after 1 year, So, it is necessary for everyone to attain dental health checkups to look at the health of mouth, find existing problems and discuss planned treatments. It helps to take further steps to minimize future problems of the oral cavity. DOI: http://doi.dx.org/10.3329/bjdre.v2i2.16244 Bangladesh Journal of Dental Research & Education Vol.2(2) 2012: 47-51